Struktur dan Fitur Linguistik Pendahuluan Artikel Sastra: Studi Retorika pada JoLLA dengan Pendekatan Problem Justifying Project - Ahmad Abdul Karim; Kusubakti Andajani; Moch Syahri (Indonesian Language Education and Literature, 2026)
Penelitian ini dilakukan untuk membedah pola retorika bagian pendahuluan artikel kajian sastra dalam jurnal JoLLA. Penelitian memanfaatkan pendekatan kualitatif dan metode studi teks yang bertumpu pada model Problem Justifying Project (PJP). Peneliti juga memanfaatkan teori ejaan, diksi, kalimat efektif, gaya bahasa, istilah asing, dan konsistensi untuk melihat konstruksi retorika. Sumber data penelitian 30 artikel kajian sastra yang dimuat dalam jurnal JoLLA. Data kajian berupa teks wacana struktur, kebahasaan, dan isi pendahuluan. Teknik pengumpulan data dilakukan melalui pembacaan mendalam, pencatatan data relevan, serta studi literatur untuk memperkaya analisis. Teknik analisis data meliputi tabulasi, interpretasi, dan penarikan simpulan terhadap hasil interpretasi. Hasil penelitian menunjukkan bahwa pola retorika bagian pendahuluan artikel kajian sastra dalam JoLLA mengikuti struktur retorika standar yang meliputi pengenalan topik, penentuan research gap, dan pernyataan tujuan penelitian. Para penulis artikel secara konsisten menggunakan strategi retorika untuk menarik perhatian pembaca, menegaskan relevansi penelitian, dan membangun kerangka konseptual. Namun, terdapat variasi penggunaan fitur linguistik, seperti pemilihan bahasa formal dan nonformal dan keberagaman tingkat eksplisitasi argumen. Temuan tersebut mencerminkan gaya penulisan yang adaptif dalam praktik publikasi ilmiah bidang sastra. Implikasi penelitian ini menunjukkan bahwa pemahaman terhadap pola retorika pendahuluan dan penggunaan fitur linguistik dapat menjadi acuan bagi penulis akademik, khususnya peneliti bidang sastra dalam menyusun pendahuluan artikel yang lebih sistematis, argumentatif, dan sesuai dengan konvensi penulisan ilmiah pada jurnal bereputasi. Selain itu, hasil penelitian ini juga dapat dimanfaatkan sebagai rujukan dalam pembelajaran penulisan akademik dan pengembangan pedoman retorika artikel ilmiah di perguruan tinggi. Structure and Linguistic Features of Introduction to Literary Articles: Rhetorical Studies on JoLLA with a Problem Justifying Project Approach This study was conducted to examine the rhetorical patterns of the introduction sections in literary studies articles published in the JoLLA journal. The research employed a qualitative approach and a text study method grounded in the Problem Justifying Project (PJP) model. In addition, the study utilized theories of spelling, diction, effective sentence construction, stylistic features, the use of foreign terms, and consistency to analyze the rhetorical construction of the texts. The data source consisted of 30 literary studies articles published in JoLLA. The research data comprised discourse texts related to the structural, linguistic, and content features of the introduction sections. Data collection was carried out through close reading, the documentation of relevant data, and a literature review to enrich the analysis. The data analysis techniques included tabulation, interpretation, and drawing conclusions based on the results of the interpretation. The findings indicate that the rhetorical pattern of the introduction sections in literary studies articles published in JoLLA generally follows a standard rhetorical structure consisting of topic introduction, identification of the research gap, and the statement of research objectives. The authors consistently employ rhetorical strategies to attract readers’ attention, emphasize the relevance of the study, and construct a conceptual framework. However, variations are observed in the use of linguistic features, such as the selection between formal and less formal language and differences in the degree of explicitness in argumentation. These findings reflect an adaptive writing style within the scholarly publication practices in the field of literary studies. The implications of this study suggest that an understanding of rhetorical patterns in introduction sections and the use of linguistic features can serve as a reference for academic writers, particularly researchers in literary studies, in composing more systematic and argumentative introductions that align with the conventions of scholarly writing in reputable journals. Furthermore, the results of this study may also be utilized as a reference in academic writing instruction and in the development of rhetorical guidelines for scientific articles in higher education.